Influenza virus carrying an R292K mutation in the neuraminidase gene is not transmitted in ferrets - Herlocher, M.L; Carr, J; Ives, J; Elias, S; Truscon, R; Roberts, N; Monto, A.S (Antiviral research, 2002)
A model of influenza transmission has been established in ferrets in which wild-type influenza infection in a donor ferret can be transmitted sequentially to other ferrets. We have studied the transmission in ferrets of a clinical isolate of A/Sydney/5/97 (H3N2) carrying the neuraminidase 292K mutation compared with the corresponding wild-type virus from the same subject. Donor ferrets ( n=four per group) were inoculated intranasally with mutant or wild-type virus and each housed with three naı̈ve contact ferrets. All donor ferrets inoculated with wildtype virus were productively infected and transmitted virus to all 12 contacts, who in turn had high viral titres in their nasal washes. In contrast, only two of the donor ferrets inoculated with mutant virus were productively infected. There was little or no evidence that the two infected donor animals transmitted mutant virus to their contact animals. This ferret model has demonstrated that the mutant influenza virus with lysine at position 292 of the neuraminidase is of reduced infectivity and does not transmit under conditions in which the wild-type virus with arginine at position 292 readily transmits.